2013
DOI: 10.3314/mmj.54.285
|View full text |Cite
|
Sign up to set email alerts
|

An Autopsy Case of Tension Pneumothorax due to the Rupture of Intrapulmonary Cavity by Mucormycosis during Treatment with a Ventilator

Abstract: A 50-year-old man with chronic renal failure (hemodialysis treatment) and interstitial pneumonia (IP) was referred to our hospital for exacerbation of IP. We immediately administered a mechanical ventilation, broad spectrum antibiotics, steroid pulse therapy, and endoxan pulse therapy in the intensive care unit, but alveolar opacities became worse. Subsequently, an intrapulmonary cavity appeared in the left middle lung field on the chest X-ray and we also administered amphotericin B. However he died of tension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…However, the presence of necrotizing cystic changes resulting in spontaneous pneumothorax is an uncommon imaging feature associated with PM [4]. To date, there have been a few documented cases of pneumothorax in PM, some of which were iatrogenic during mechanical ventilation or bronchoscopic intervention and only one prior reported case of spontaneous pneumothorax due to PM [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of necrotizing cystic changes resulting in spontaneous pneumothorax is an uncommon imaging feature associated with PM [4]. To date, there have been a few documented cases of pneumothorax in PM, some of which were iatrogenic during mechanical ventilation or bronchoscopic intervention and only one prior reported case of spontaneous pneumothorax due to PM [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…In our literature review, we identified a small number of cases of pneumothorax occurring in the context of pulmonary mucormycosis are noted with iatrogenic causes (mechanical ventilation and bronchoscopy),15 pneumothorax occurring spontaneously in the presence of mucormycosis and methicillin-resistant staphylococcus aureus (MRSA) in an immunocompromised patient,16 and in combination with Aspergillus in a patient on dialysis 17. However,` only one other case is noted to have occurred with a spontaneous pneumothorax of a non-iatrogenic aetiology in the absence of proven co-infection 18…”
Section: Discussionmentioning
confidence: 99%
“…There are few case reports of pneumothorax in pulmonary mucormycosis, some of which are iatrogenic during mechanical ventilation and bronchoscopic procedure [9–11] . Combined mucormycosis and methicillin-resistant staphylococcus aureus (MRSA) were found to be responsible for life threatening pneumothorax in an immunocompromised patient [12] .…”
Section: Discussionmentioning
confidence: 99%